Review COVID- 19 Pandemic: The Implications for Diabetes Care and Specifics Management - Al- Awar, Mohammed Sadeg; Al- Qalah, Talal Ali; Omer, Ammar; Al- Agme, Faisal (Journal of medical and pharmaceutical sciences, 2020)
Background. The coronavirus disease 2019 (COVID- 19) pandemic has emerged as one of the greatest challenges faced by humankind in the recent past. People with diabetes and related comorbidities are at increased risk of its complications and of COVID- 19- related death. Older age, multimorbidity, hyperglycemia, cardiac injury and severe inflammatory response are predictors of poor outcome. Aims. This article summarizes current data on the clinical presentation and risks of COVID- 19 in diabetic patients. We also provide some recommendations for the management of diabetic patients with COVID- 19. Results: According. to current data, diabetic patients do not appear to be at increased risk of contracting SARS- CoV- 2 compared to the general population. On the other hand, diabetes is a risk factor for developing severe and critical forms of COVID- 19, the latter requiring admission to an intensive care unit and/or use of invasive mechanical ventilation, with high mortality rates. The characteristics of diabetic patients at risk for developing severe and critical forms of COVID- 19, as well as the prognostic impact of diabetes on the course of COVID- 19, are under current investigation. Obesity, the main risk factor for incident type 2diabetes, is more common in patients with critical forms of COVID- 19 requiring invasive mechanical ventilation. On the other hand, COVID- 19 is usually associated with poor glycemic control and a higher risk of ketoacidosis in diabetic patients. There are currently no recommendations in favour of discontinuing antihypertensive medications that interact with the renin-angiotensin-aldosterone system. Metformin and Sodium-glucose transport protein- 2)SGLT2( inhibitors should be discontinued in patients with severe forms of COVID- 19 owing to the risks of lactic acidosis and ketoacidosis. Conclusion: There are currently no data showing an increased risk of contracting COVID- 19 in diabetic patients. On the other hand, diabetic patients require special attention, since diabetes is associated with a higher risk of severe, critical, and fatal forms of COVID- 19. Our knowledge about this new Coronavirus progresses day by day. Ongoing studies will make it possible to better define the profile(s) of diabetic patients at increased risk of poor prognosis. In any case, the importance of blood glucose monitoring and control over the course of the infection should be emphasized, as well as that of screening for (pre) diabetes in all patients with a confirmed infection by COVID- 19.